2020
DOI: 10.26832/24566632.2020.050103
|View full text |Cite
|
Sign up to set email alerts
|

Role of credit in maize (Zea mays L.) production and assessment of food security in a selected area of Bangladesh

Abstract: Credit provides the means for many farmers to adjust their operations to keep up with the constant changes and, by doing so, to improve their operations. It also contributes to achieve food security of households. Tabular method is used to analyze credit profile, multiple regression analyses are used to determine the impact of credit on maize production and "Modified" OECD scale is used to measure calorie intake level of the 60 maize farming households who has got agricultural credit from Rajshahi Krishi Unnay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This protein intake was also lower than as reported by Rahman et al (2007) in their research which was amounted to 54.64 gm. Among the food items per capita yearly rice, fish and meat consumption among the surveyed enclaves household members was 222.41 , 14.47 and 10.47 Kg which was far higher than the national average of 181.3 , 13.51 and 9.12 Kg (FAO, 2021b;Selvanathan et al, 2020;Rahman, 2020;FAO, 2009).…”
Section: Food Consumption Calorie Intake and Protein Intake Of Sample...mentioning
confidence: 83%
See 1 more Smart Citation
“…This protein intake was also lower than as reported by Rahman et al (2007) in their research which was amounted to 54.64 gm. Among the food items per capita yearly rice, fish and meat consumption among the surveyed enclaves household members was 222.41 , 14.47 and 10.47 Kg which was far higher than the national average of 181.3 , 13.51 and 9.12 Kg (FAO, 2021b;Selvanathan et al, 2020;Rahman, 2020;FAO, 2009).…”
Section: Food Consumption Calorie Intake and Protein Intake Of Sample...mentioning
confidence: 83%
“…If the calorie intake is above 1600 Kilo calorie but less than 1805 Kilo calorie than the person is termed as in hard core poverty line. Absolute poverty line is termed when a person's daily intake is above 1805 Kilo 356 RAHMAN AND KHATUN calorie but less than 2122 Kilo calorie (BER, 2020;Saha et al, 2021;Akter et al, 2020).…”
Section: Poverty Measurementmentioning
confidence: 99%
“…Studying the maize cultivation, Akter et al (2020) identified that credit had a positive effect on fertilizer demand as well as on irrigation demand and, ultimately, a positive impact on maize production. The study used multiple regression analyses to analyze the effect of credit on maize production; it also used the "Modified" OECD scale to measure calorie intake level.…”
Section: Literature Reviewmentioning
confidence: 99%